Measuring the Unmeasured: Exploring the Concept of “Supply Chain Quotient” [SCQ] - N. Sureshkumar PP Narayanan; Farha Ghapar; Li Lian Chew; Veera Pandiyan Kaliani Sundram; Umahdevi Jayamani; Azlina Muhammad (Information Management and Business Review, 2024)
The concepts of intelligence quotient (IQ) and emotional quotient (EQ) have long been recognized as essential indicators of cognitive and emotional capabilities. However, the field of supply chain management lacks a standardized measure to assess the competencies required for successful supply chain operations. This article aims to fill this gap by introducing the concept of Supply Chain Quotient (SCQ) as a novel measure of supply chain competence. The SCQ framework expands beyond traditional intelligence and emotional factors, considering the unique skills and characteristics required in the complex world of supply chains. Drawing from existing literature on supply chain management, human resources, and cognitive psychology, this research explores the key dimensions and components that comprise the SCQ. The paper also examines potential methodologies and approaches for assessing and quantifying the SCQ, including self-assessment tools, case studies, and behavioral assessments. By introducing the SCQ, this research contributes to the understanding and evaluation of supply chain competence, providing organizations with a framework to identify, develop, and leverage talent in their supply chain functions. Additionally, it opens avenues for future research and practical applications to enhance supply chain performance and improve overall organizational outcomes.